Роль автоматизованого тестування у сучасній розробці програмного забезпечення - Коробов, І. Р. (ХНУРЕ, 2023)
Automated testing is crucial in modern software development due to the complexity of software applications. It offers faster test cycles, increased test coverage, and more accurate results compared to manual testing. Effective test cases should be clear, concise, and cover all relevant scenarios. The main advantages of automated testing are speed, consistency, and continuous testing. Best practices include identifying the right tools and frameworks and incorporating automated testing into the software development lifecycle. The role of automated testing in modern software development is crucial for ensuring software quality and reliability